Analisa % FFA, PH dan Massa Jenis pada Campuran Minyak Jelantah dan Minyak Kelapa - Ariyani Debora; Megawati Eka; Yuniarti (Kodepena (Komunitas Dosen Penulis dan Peneliti Indonesia), 2024)
The increase in population and increasing human needs along with the times has resulted in an increasing need for non-renewable energy. To reduce dependence on petroleum fuels, one way is to produce biodiesel fuel whose raw materials are obtained from plants. Biodiesel is a fuel that contains ester compounds from plants and animal fats and can be used as an alternative fuel with great potential as a substitute for diesel. This form of methyl ester or ethyl ester compound is environmentally friendly, non-toxic and economical. Coconut (Cocos nucifera) is a type of plant that has one glycerin unit and a number of fatty acids in every coconut oil molecule. Coconut oil has the potential to produce Coco methyl ester which can be used as a raw material for biodiesel. Used cooking oil is used oil from household (domestic) fryers whose remaining frying results or waste is immediately thrown into the environment. According to research from Kumar, the use of coconut oil as a raw material for making biodiesel is able to streamline time and the use of chemicals as solvents in the transesterification process. Before carrying out this research, a preliminary test should be carried out, by testing the %FFA, pH and density of the mixture of used cooking oil and coconut oil. This was done as a reference for further research. The %FFA in the mixture of used cooking oil and coconut oil was the highest at a ratio of 75: 25 (MJ: MK) %FFA value: 4.4%. The pH of the mixture between used cooking oil and coconut oil has the same value, namely: 5 and the specific gravity obtained is: 0.8 gram/ml Keywords: of used cooking oil, coconut oil, % FFA, pH and Specific gravity